Changes in the As solid speciation during weathering of volcanic ashes: A XAS study on Patagonian ashes and Chacopampean loess. (1st September 2017) - Bia, G.; García, M.G.; Borgnino, L.
Abstract: X-ray absorption spectroscopy (XAS) was used to determine the oxidation state of As, local chemical coordination and the relative proportion of different As species in recent and ancient Andean volcanic ashes, as well as in Chaco Pampean loess. As K edge XANES analysis indicates that in loess sediments the dominant species is As(V) (i.e., >91%). Conversely, As(III) is dominant in all ash samples. In the Puyehue sample, only As(III) species were determined, while in both, the Chaitén and the ancient tephra samples, As(III) species accounts for 66% of the total As. The remaining 34% corresponds to As(−1) in the Chaitén sample and to As(V) in the weathered tephra. The proposed EXAFS models fit well with the experimental data, suggesting that in ancient and recent volcanic ashes, As(III) is likely related to As atoms present as impurities within the glass structure, forming hydroxide species bound to the Al-Si network. In addition, the identified As(−1) species is related to arsenian pyrite, while in the ancient volcanic ash, As(V) was likely a product of incipient weathering. In loess sediments, the identified As(V) species represents arsenate ions adsorbed onto Fe oxy(hydr)oxides, forming inner-sphere surface complexes, in a bidentate binuclear configuration.